Los jingles en las campañas de las elecciones seccionales de ecuador, caso provincia de el Oro - Torres Miranda, Xiomara Carolina; Arias Muquinche, Leyton Gino (Machala, 2023)
This study aims to analyze how political jingles are integrated into political campaign strategies and their close relationship with popular music. The focus of the research is on the sectional elections of Ecuador in 2023, specifically on the candidacy of the El Oro province. Methodologically, this study adopts a mixed approach. Data collection will include interviews with campaign strategists and music producers experienced in the political field; a content analysis to discern the characteristics of the musical pieces used in the campaign; and surveys of voters to gauge their perception of the music and its potential influence on voting decisions. The results seek to provide a theoretical contribution and, simultaneously, offer recommendations to composers, advisors, and candidates on how to effectively engage voters through music.
Este trabajo se propone analizar cómo los jingles políticos se incorporan en las estrategias de las campañas políticas y su relación íntima con la música popular. El foco del estudio se centra en las elecciones seccionales de Ecuador de 2023, particularmente en las candidaturas de la provincia de El Oro. En términos metodológicos, este estudio adopta un enfoque mixto. La recolección de datos incluirá entrevistas a estrategas de campaña y productores musicales con experiencia en el ámbito político; un análisis de contenido para discernir las características de las piezas musicales empleadas en campaña; y encuestas a votantes para sondear su percepción acerca de la música y su potencial influencia en la decisión del voto. Los resultados buscan brindar una contribución teórica y, simultáneamente, ofrecer recomendaciones a compositores, asesores y candidatos sobre como impactar eficazmente a los votantes mediante la música.
Keywords: JINGLES POLITICOS; MUSICA POPULAR; CAMPAÑAS ELECTORALES; ESTRATEGIAS DE CAMPAÑA; COMUNICACION POLITICA